2017
DOI: 10.1016/j.drudis.2017.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics for Drug Discovery: an industry-driven effort to target drug residence time

Abstract: A considerable number of approved drugs show non-equilibrium binding characteristics, emphasizing the potential role of drug residence times for in vivo efficacy. Therefore, a detailed understanding of the kinetics of association and dissociation of a target-ligand complex might provide crucial insight into the molecular mechanism-of-action of a compound. This deeper understanding will help to improve decision making in drug discovery, thus leading to a better selection of interesting compounds to be profiled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
189
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 188 publications
(190 citation statements)
references
References 112 publications
(135 reference statements)
0
189
0
1
Order By: Relevance
“…1826 In addition, the role of binding kinetics has been explored in forward-thinking programs, such as the K4DD Innovative Medicines Initiative. 27 The present Review reiterates some of the basic concepts that govern drug–target interactions and shows that access to the on and off rates for formation and breakdown of the drug–target complex provides an additional dimension of information that can be used to prioritize drug leads based on kinetic selectivity. Subsequently it is shown that the translation of kinetic effects to time-dependent changes in drug activity depends on target vulnerability which directly impacts kinetic selectivity.…”
Section: Introductionmentioning
confidence: 94%
“…1826 In addition, the role of binding kinetics has been explored in forward-thinking programs, such as the K4DD Innovative Medicines Initiative. 27 The present Review reiterates some of the basic concepts that govern drug–target interactions and shows that access to the on and off rates for formation and breakdown of the drug–target complex provides an additional dimension of information that can be used to prioritize drug leads based on kinetic selectivity. Subsequently it is shown that the translation of kinetic effects to time-dependent changes in drug activity depends on target vulnerability which directly impacts kinetic selectivity.…”
Section: Introductionmentioning
confidence: 94%
“…Therefore, the thermodynamic and kinetic measures of binding are linked as K d = k off / k on . However, in most cases, high‐affinity ligands can sometimes exhibit unexpectedly poor pharmacological efficacy in vivo, and a considerable number of approved drugs have manifested nonequilibrium binding characteristics, thereby highlighting why the potential role of drug‐binding kinetics in in vivo efficacy has attracted extensive attention . Here, it should be noted that binding kinetics is only one of many parameters that affect in vivo efficacy of drugs.…”
Section: Computational Methods For Cbddmentioning
confidence: 99%
“…There is a growing understanding that measuring the affinity at equilibrium may not be the best predictor of the in vivo efficacy of a compound, as a number of clinically approved drugs show non‐equilibrium modes of binding (Hothersall, Brown, Dale, & Rawlins, ; Kola & Landis, ; Schuetz et al, ; Waring et al, ). Equilibrium affinity is a function of the association and dissociation rate constants ( K D = k off / k on ) of a molecule binding to a receptor, and compounds with the same affinity can have different association and dissociation rates.…”
Section: Ligand‐binding Kineticsmentioning
confidence: 99%
“…There is a growing understanding that measuring the affinity at equilibrium may not be the best predictor of the in vivo efficacy of a compound, as a number of clinically approved drugs show non-equilibrium modes of binding (Hothersall, Brown, Dale, & Rawlins, 2016;Kola & Landis, 2004;Schuetz et al, 2017;Waring et al, 2015). Equilibrium F I G U R E 2 Measuring ligand binding using fluorescence-or radioactive-based approaches.…”
Section: Ligand-binding Kineticsmentioning
confidence: 99%